2017
DOI: 10.2106/jbjs.cc.16.00262
|View full text |Cite|
|
Sign up to set email alerts
|

Isolated Scapular Metastasis in a Patient with Malignant Struma Ovarii

Abstract: Malignant struma ovarii with bone metastases is very rare, and its diagnosis is a challenge. There are some documented cases with bone metastases, mostly to the thoracic and lumbar spine. The optimal treatment of choice for the bone lesion is unknown because of the rarity of its presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…This report is the first in the literature to conclude that the outcome is related to the type of cancer. Studies have increasingly advocated for radioactive iodine therapy (12), but our study found that the mortality in the radioiodine treatment group was reduced by 1.5% compared with that in the patients who did not receive radioiodine treatment, but the difference was not statistically significant. As mentioned above, MSO is rare and difficult to find and diagnose, especially in those with nonpapillary thyroid cancer.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This report is the first in the literature to conclude that the outcome is related to the type of cancer. Studies have increasingly advocated for radioactive iodine therapy (12), but our study found that the mortality in the radioiodine treatment group was reduced by 1.5% compared with that in the patients who did not receive radioiodine treatment, but the difference was not statistically significant. As mentioned above, MSO is rare and difficult to find and diagnose, especially in those with nonpapillary thyroid cancer.…”
Section: Discussioncontrasting
confidence: 70%
“…Because it is prone to malignant transformation, the management of cases of MSO is still controversial. Most authors (11) have advocated for an aggressive treatment based on local surgery, followed by postoperative adjuvant treatment, including total thyroidectomy (12,13) and radioactive iodine 131 (I-131) therapy, especially when distant metastases are present.…”
Section: Introductionmentioning
confidence: 99%
“…Favorable survival rates (95.3%, 88.7%, and 88.7% at 5, 10, and 20 years of OS, respectively) were found regardless of treatment. Therefore, the overall prognosis of MSO is relatively good, but pulmonary and bone metastases of MSO have been reported in recent years [14, 15]. Therefore, all cases of MSO should be followed regularly for at least 10 years after operation and adjuvant therapies.…”
Section: Discussionmentioning
confidence: 99%